Pengaruh Waktu Penyangraian Beras terhadap Komponen Bioaktif pada Bekasam Ikan Nila (Oreochromis niloticus) - Rinto Rinto; Indah Widiastuti; Susi Lestari; Dwi Inda Sari; Putri Ayu Anisa (Universitas Sriwijaya, 2021)
The objective of this research was to determine the effect of rice roasting time on bioactive compounds in bekasam from tilapia. This research used a Randomized block Design with four treatments. The treatments were the production of bekasam used rice (as a control) and rice with roasting time (0, 5, 10, 15 minutes). The parameters observed were acidity level (pH), lovastatin, peptide, and n-amino contents. The results of this study indicate that, roasting rice had a significant effect on the lovastatin content (54.35-57.73 ppm), where the highest lovastatin content was bekasam was produced by rice treatment (control). Rice roasting gived no significant affect to the pH value (6.12-6.35), peptide (9.24%-14.28%), and n-amino (0.014%-0.028%). Based on results of the research, fermentation bekasam process of tilapia fish with rice and rice roasting in the vacuum packaging has not been perfect.